2016
DOI: 10.1016/j.jpsychores.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Fathers and mothers with eating-disorder psychopathology: Associations with child eating-disorder behaviors

Abstract: Objective A limited literature suggests an association between maternal eating disorders and child feeding difficulties, and notes maternal concern about inadvertently transmitting eating disorders. Thus, parents may be an important target for eating-disorder research to guide the development of clinical programs. Methods The current study examined differences in child eating-disorder behaviors and parental feeding practices between a sample of parents (42 fathers, 130 mothers) exhibiting core features of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 52 publications
1
21
1
1
Order By: Relevance
“…Yeme davranışları üzerine yapılan araştırmaların çoğu anne odaklı yapılmakta ve çocuklarının beslenmeleri hakkındaki endişelerini belirlemeye çalışmaktadır. Anneler, yeme problemi olan çocuklarının, yeme bozukluğunun çocuklarına olumsuz etkilerini önlemek veya bunlara değinmek için tedavi arayışlarına yönelmiştir [11]. Çünkü yeme bozukluğu riski taşıyan çocukların en kısa sürede belirlenmesi ve önleme programlarının uygulanmasının daha sonraki yıllarda oluşabilecek yeme bozukluğu riskini azaltabileceği görüşü hakimdir [12].…”
Section: Introductionunclassified
“…Yeme davranışları üzerine yapılan araştırmaların çoğu anne odaklı yapılmakta ve çocuklarının beslenmeleri hakkındaki endişelerini belirlemeye çalışmaktadır. Anneler, yeme problemi olan çocuklarının, yeme bozukluğunun çocuklarına olumsuz etkilerini önlemek veya bunlara değinmek için tedavi arayışlarına yönelmiştir [11]. Çünkü yeme bozukluğu riski taşıyan çocukların en kısa sürede belirlenmesi ve önleme programlarının uygulanmasının daha sonraki yıllarda oluşabilecek yeme bozukluğu riskini azaltabileceği görüşü hakimdir [12].…”
Section: Introductionunclassified
“…As described elsewhere [33], parent groups were formed using items from the EDE-Q and the QEWP-R. The “parent BED” group criteria required binge-eating at least weekly for three months, no weekly purging, and at least moderate distress.…”
Section: Methodsmentioning
confidence: 99%
“…In humans, it is still under investigation if obesity or maternal overnutrition during pregnancy leads to the development of food addiction in the offspring. Initial reports found that children from obese mothers or mothers with eating disorders presented more binge eating and night eating [ 54 , 55 ] and consumed more carbohydrates compared to their normal weight counterparts [ 56 ]. Also, a positive correlation between addicted parents and food addiction in their offspring has been proven [ 57 ], although epidemiological studies are needed to support these findings.…”
Section: Potential Role Of Fetal Programming By Hypercaloric Food mentioning
confidence: 99%